Herbal and alternative medicine use: a cross sectional study to evaluate the prevalence and predictors of use in cancer patients - Al-Masri, Mahmoud; Darwish, Rula; Safi, Yasmin; Mustafa, Aseel; Alzyoud, Dina; Almasri, Mohammad; Kahhaleh, Bilal; Khader, Mohammad (Frontiers in Pharmacology, 2025)
BackgroundHerbal and alternative medicine is increasingly used among cancer patients to manage disease, symptoms, and improve quality of life. Reported usage rates worldwide vary from 3.5% to 90%. Understanding prevalence and predictors of such use is essential for safety and efficacy, especially considering potential interactions with conventional treatments.MethodsThis cross-sectional study aimed to evaluate the prevalence and predictors of herbal medicine use among cancer patients in Jordan. All cancer patients, including pediatric and adult patients who can give consent or assent, were included in the study.ResultsOut of 602 patients surveyed, 163 (27.1%) reported using herbal medicine. Among users, 68.7% were female, 52.9% had lower education levels, and 60% were unemployed. Of the key predictors: lower income (OR = 3.24, p = 0.021) and self-perceived knowledge of herbal medicine (OR = 18.9, p < 0.001). Knowledge assessment revealed that 54% relied on social media for information, while only 11% consulted healthcare professionals. Between 60% and 80% of patients were unaware of potential interactions between herbal treatments and cancer therapies. Additionally, the 85% reported that their healthcare providers did not inform them about these risks. Reasons for using herbs and alternative included maintaining health (52.4%) and cancer treatment (47.6%). Among non-users, 29% doubted its effectiveness, and 34% felt uninformed.ConclusionThe study revealed that low income and high self-perceived awareness about herbal medicine are key predictors of herbal usage. However, there is a significant knowledge gap, with many patients relying on social media and being unaware of potential interactions with oncology treatments. Customized educational interventions are needed to address these factors.